Pengaruh Penggunan Model Pembelajaran Tipe Two Stay Two Stray (TSTS) Terhadap Hasil Belajar Pada Materi Sistem saraf di SMA Negeri 2 Pulau Taliabu - Sarianti Sarianti; Moh. Fahri Haruna; Nurlia Nurlia (Universitas Muhammadiyah Luwuk, 2022)
Abstract: The purpose of this study was to determine the effect of using the Two Stay Two Stray (TSTS) cooperative learning model on student learning outcomes in class XI MIPA 1 SMA Negeri 2 Pulau Taliabu. This research was carried out in the even semester of the 2020/2021 Academic Year from April to May 2021. The research design was in the form of a Pretest Posttest Control Group Design. The population of all students in class XI, amounting to 86 students. The research sample consisted of an experimental class with 22 students and a control class with 22 students, so that the total sample size was 44 students. The instrument used is test questions, in the form of pretest and posttest with a total of 20 multiple choice questions each. The data collected from the test results is processed and tested using the t-test (t-test). to see the influence of the learning model, then to test the hypothesis using the F test, with a significant α = 0.05. Based on the results of the study, the value of tcount > ttable (2.887> 1.682) was obtained, so that it was found that there were differences in the effect of learning outcomes with conventional learning models and two stay two stray learning models. So it can be concluded that there is a significant effect of using the two stay two stray (TSTS) type learning model on student learning outcomes in class XI MIPA 1 SMA Negeri 2 Pulau Taliabu. Keywords: Cooperative Learning; Pulau Taliabu ; Two Stay Two Stray